My Curious Day with George: Dr. Szekely Prescribes Play to a Visiting Artist-Teacher - Weir, Jamia (The Canadian Art Teacher / Enseigner les arts au Canada, 2023)
This article presents a personal visit between art teacher/artist, Jamia Weir and Dr. George Szekely, a well known figure in the field of art education and a proponent of “Play Based Art Education.” Weir outlines ideas and sentiments gleaned from a day “picking the brain” of her “art teacher hero.” The conversation took place in the Hudson River Valley in July of 2021.